Cele ideowe i struktura organizacyjna Wszechzwiązkowej Organizacji Pionierskiej imienia W.I. Lenina oraz jej miejsce w systemie wychowanie nowego człowieka (homo sovieticus) - Grzybowski, Romuald (Biuletyn Historii Wychowania, 2017)
One of the characteristics of the second half of the 19th and 20th centuries was the tendency of young people to gather in youth associations and organisations. Some of these were created spontaneously and their activities were illegal, while others were created by the authorities of particular states, especially totalitarian ones. One example of such an organisation was the All-Union Pioneer Organisation, established by the leaders of the Bolshevik Revolution in Russia in 1922. Its strategic goal was to participate in the education of the new man, who was to become homo sovieticus, a higher variety of homo sapiens, in the future. The Pioneer Organisation fulfilled this task by organising children of school age (aged 9 to 14) and subjecting them to a systematic ideological and political training based on the Leninist or Stalinist model. The activities of the Pioneer Organisation were supervised by the Komsomol and additionally by the leadership of the communist party ruling the USSR. The structure of the Pioneer Organisation included groups, packs and cells. Like the Komsomol, the Pioneer Organisation also had its symbols, such as the threepointed red scarf that symbolised three generations: communists, komsomolets and pioneers, as well as a pioneer badge, a pioneer salute, a uniform, bugles and a snare drum.